2011
DOI: 10.1074/jbc.m110.195958
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a Filamin Four-domain Fragment and the Influence of Splicing Variant-1 on the Structure

Abstract: Filamins are large actin-binding proteins that stabilize threedimensional F-actin networks and link them to the cell membrane by binding to transmembrane receptors, e.g. integrins or ion channels. In addition, filamins bind to various other proteins with diverse function, including signaling and adaptor proteins, such as migfilin (1-6). Accordingly, filamins are considered as scaffolding proteins that integrate multiple cellular functions. Filamins are also associated with various human genetic diseases includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
(114 reference statements)
1
14
0
Order By: Relevance
“…We co-expressed wild-type or mutant Myc-RhoGDI2-HA with Flag-tagged FLNA or a FLNA del41 variant in Hela cells. FLNA del41 removes the auto-inhibitory domain (strand A) of repeat 20 from repeat 21 constitutively revealing its cryptic binding site [3133] (Figure 2A). Wild-type RhoGDI2 failed to co-immunoprecipitate either form of FLNA, whereas mutant RhoGDI2(Y153E) collected FLNA even though the expression level of mutant RhoGDI2(Y153E) was lower than that of wild-type.…”
Section: Resultsmentioning
confidence: 99%
“…We co-expressed wild-type or mutant Myc-RhoGDI2-HA with Flag-tagged FLNA or a FLNA del41 variant in Hela cells. FLNA del41 removes the auto-inhibitory domain (strand A) of repeat 20 from repeat 21 constitutively revealing its cryptic binding site [3133] (Figure 2A). Wild-type RhoGDI2 failed to co-immunoprecipitate either form of FLNA, whereas mutant RhoGDI2(Y153E) collected FLNA even though the expression level of mutant RhoGDI2(Y153E) was lower than that of wild-type.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports revealed that the N-terminus of Ig20 forms a β-strand that interacts with, and occupies, the C and D β-strands (known as the CD face) of the adjacent Ig21. [26][27][28] When mechanical stresses stretch the FLNA protein, the masked CD face is exposed, increasing the affinity of Ig21 toward its binding partners, including integrins and migfilin, and leading to downstream signaling. 29 In this study, the exon-skipped FLNA protein had stronger binding to β7 and a similar capacity to induce focal adhesions, compared with that of wild-type FLNA.…”
Section: Discussionmentioning
confidence: 99%
“…4D. This ensures a precise and well-controlled gating curve even though the involved binding energies lie below 4 k B T. It has been argued that an autoinhibition of filamin seems unlikely in in vitro experiments because it could be shown that an excess of ligand alone is able to convert the filamin domain pairs from a closed to an open conformation (33,34). However, this stood in apparent contrast to earlier reports that the isolated domain 21 binds stronger to ligands than the domain pairs (14) as well as to binding studies on strained filamin-cross-linked actin networks (17).…”
Section: Discussionmentioning
confidence: 99%